The Development of a Causal Model of Self-care Behaviors of AIDS Patients in Antiretroviral Drugs Clinic, Phayuha Khiri Hospital Nakhon Sawan Province - Chompoopoo , Siripun (Journal of Disease and Health Risk DPC.3, 2023)
HIV/AIDS is a disease that has no cure, however, knowledge about HIV/AIDS has progressed. One way to help alleviate the problem of AIDS is to use antiretroviral drugs, and the use of multiple antiretroviral drugs together is the best treatment for HIV/AIDS. For all patients to take the medication regularly, self-care behavior is essential. This research aimed to 1) find factors and components related to the self-care behavior of HIV-infected patients; 2) develop a causal relationship model that affects the self-care behavior of HIV-infected patients; and 3) find suggestions for the use of research results according to the model of self-care behavior of HIV-infected patients in the antiretroviral drug clinic. The research was a mixed method sequential design, consisting of two research phases: Phase 1, collecting quantitative data, and Phase 2, collecting qualitative data. The population was patients registered for treatment at the antiretroviral drug clinic, for a total of 238 people. This research studied the real population. Data were analyzed by percentages, means, Pearson correlation coefficients, and structural equations. The results showed that the ratio of men to women was similar, namely 56.7%:43.3%, aged between 46 and 60 years, educational level was primary school 51.7%, average monthly income was 9,133.29 baht, and the status showed that most of the samples were married, 42.9%, with more than half of the patients, 58.8%, having been ill for more than 10 years or more. The factors related to the self-care behavior of HIV-infected people included knowledge about self-care, the ability to understand information about risk factors that affect health, the ability to assess information about risk factors that affect health, the ability to apply information to lead to decisions on actions on risk factors that affect health, patient experience, age, ability to self-care, and the ability to access information and knowledge about health information, which were statistically significant at P-value<0.01. The causal relationship model can explain the variation by 24%, according to the model. The model is consistent with the data according to the hypothesis, with a close fit (Fit) at Chi-square = 75.098, P = 0.443, DF = 74, CMIN/DF = 1.015, RMR = 0.128, GFI = 0.963, AGFI = 0.932, and RMSEA = 0.008. Relevant agencies should use the results of this research to support the planning and implementation of prevention activities according to the model of self-care behavior of HIV-infected patients in the antiretroviral drug clinic, which is suitable for the area.